Air France internet marketing : optimizing Google, Yahoo!, MSN, and Kayak sponsored search - Jeffery, Mark, (SAGE knowledge. Cases., 2016)
Rob Griffin, senior vice president and U.S. director of search for Media Contacts, a communications consulting firm, is faced with the task of optimizing search engine marketing (SEM) for Air France. At the time of the case, SEM had become an advertising phenomenon, with North American advertisers spending $9.4 billion in the SEM channel, up 62% from 2005. Moving forward, Griffin wants to ensure that the team keeps its leading edge and delivers the results Air France requires for optimal Internet sales growth. This case study examines his efforts.